2020
DOI: 10.1016/j.isci.2020.101430
|View full text |Cite
|
Sign up to set email alerts
|

A Protein Environment-Modulated Energy Dissipation Channel in LHCII Antenna Complex

Abstract: Summary The major light-harvesting complex of photosystem II (LHCII) is the main contributor to sunlight energy harvesting in plants. The flexible design of LHCII underlies a photoprotective mechanism whereby this complex switches to a dissipative state in response to high light stress, allowing the rapid dissipation of excess excitation energy (non-photochemical quenching, NPQ). In this work, we locked single LHCII trimers in a quenched conformation after immobilization of the complexes in polyacry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 65 publications
0
18
0
Order By: Relevance
“…The light-induced absorbance changes were driven by microsecond pulses monitored in the 400- to 700-nm range with microsecond temporal resolution over microsecond-to-second-long time delays. The transient absorption data were globally fit by a sum of exponential functions using Matlab (The MathWorks Inc. USA) scripts, and the confidence intervals of the resulting rate constants were estimated using bootstrap resampling as described previously ( 72 ).…”
Section: Methodsmentioning
confidence: 99%
“…The light-induced absorbance changes were driven by microsecond pulses monitored in the 400- to 700-nm range with microsecond temporal resolution over microsecond-to-second-long time delays. The transient absorption data were globally fit by a sum of exponential functions using Matlab (The MathWorks Inc. USA) scripts, and the confidence intervals of the resulting rate constants were estimated using bootstrap resampling as described previously ( 72 ).…”
Section: Methodsmentioning
confidence: 99%
“…The picture gets even more complicated when one considers quenched LHCII in gel. It was recently shown that excitation of Q y results in the immediate appearance of a large-amplitude positive peak at 19, 417cm −1 (515nm) which we'll label A 515 [61]. This is not merely a shifted S 1 as direct excitation of Lut gave the usual S 1 ESA at 18, 500cm −1 (540nm), although A 515 is detectable at later times and may simply be initially hidden by S 1 .…”
Section: Npq May Involve Non-coulomb Interactions And/or Non-adiabatic Inter-molecular Statesmentioning
confidence: 79%
“…However, as they point out, ε S 1 is not a free parameter and a protein-induced blue-shift of 14, 050 → 18, 000cm −1 (712 → 555nm) would be quite large. Saccon et al recently performed TA measurements on quenched LHCII immobilised in polyacrylamide gel (a model for NPQ) [61] and found that linear excitation of Lut (i.e. via S 2 ) produces the usual S 1 → S n ESA at ε S n − ε S 1 ≈ 18, 500cm −1 (540nm).…”
Section: Npq May Involve Modulation Of the Properties Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…S2). It has previously been observed that LH1 and LH2 antenna rings in purple bacteria for example displayed a 50% shorter lifetime in vivo compared to in vitro (Ricci et al, 1996) and similarly that quenching in LHCII was dependent on its membrane environment (Moya et al, 2001, Natali et al, 2016, Saccon et al, 2020, Manna et al, 2021. Lifetimes of pigmentprotein complexes largely depend on their local environment, e.g.…”
Section: Less Qh In Isolated System Compared To Intact Onesmentioning
confidence: 95%